2017
DOI: 10.3389/fmars.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Cairns: Biologging Improves the Use of Seabirds as Sentinels of the Sea

Abstract: In 1987, David Cairns proposed that a gradient of colony-based measures on seabirds could be used to assess food supply in the ocean. Measures closely tied to the ocean, such as foraging trip duration, would be sensitive to small declines in food supply while measures more closely tied with the nest site, such as reproductive success, would be sensitive to large declines in food supply. The continual refinement of tracking devices holds the potential to clearly link variables measured via seabirds to food supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Finally, individual foraging plasticity may prevent the use of apex predators as ecological indicators of lower trophic levels (Gr emillet & Charmantier 2010). This is particularly relevant as seabird populations are being flagged as indicators of food supplies within marine systems (Boyd et al 2015;Brisson-Curadeau et al 2017). and INDEXPUF, and by the OSU OREME Montpellier.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, individual foraging plasticity may prevent the use of apex predators as ecological indicators of lower trophic levels (Gr emillet & Charmantier 2010). This is particularly relevant as seabird populations are being flagged as indicators of food supplies within marine systems (Boyd et al 2015;Brisson-Curadeau et al 2017). and INDEXPUF, and by the OSU OREME Montpellier.…”
Section: Discussionmentioning
confidence: 99%
“…While certainly smart choices of the study species are key to successful research, typified by the Krogh principle: "for a large number of problems there will be some animal of choice, or a few such animals, on which it can be most conveniently studied" (Krogh, 1929), most terrestrial, aquatic and aerial species cannot be well observed in the field. Technological solutions to record the movements, behaviour and physiology of animals, and associated methodological advancements for analysing the data collected, have revolutionized research in animal ecology and beyond (Brisson-Curadeau, Patterson, Whelan, Lazarus, & Elliott, 2017;Kenward, 2001;Ropert-Coudert, Beaulieu, Hanuise, & Kato, 2009;Ropert-Coudert & Wilson, 2005;Weimerskirch, 2009). The general term for this technological approach to study animals is called Biologging-'the use of miniaturized animal-attached tags for logging and/or relaying data about an animal's movements, behaviour, physiology, and/or environment' (Rutz & Hays, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Progress in this broad field has been exceptional in the last decade (Baratchi, Meratnia, Havinga, Skidmore, & Toxopeus, 2013;Hussey et al, 2015;Kays, Crofoot, Jetz, & Wikelski, 2015;Wilmers et al, 2015;Brisson-Curadeau et al, 2017;Tibbetts, 2017;Harcourt et al, 2019; Lowerre-Barbieri, Kays, Thorson, & Wikelski, 2019), with exciting ongoing developments often occurring outside the field of animal ecology, including in different disciplines such as engineering, physics or computer science. As such, the Journal of Animal Ecology issued an Open Call in 2018 for a Special Feature on 'Biologging', with the aim to showcase the novel developments in the field and the range of ecological questions which can now be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Seabirds are sentinel species in the marine environment (Cairns 1988, Piatt et al 2007, Brisson-Curadeau et al 2017), yet their ecology and distribution during the nonbreeding period is poorly understood (Huettmann and Diamond 2000). This dearth of information is concerning considering that staging, migration, and wintering periods comprise the majority of the avian annual cycle, and conditions during these periods may have carryover effects that influence survival and reproduction in subsequent breeding seasons (Sorensen et al 2009, Harrison et al 2011, Salton et al 2015, Szostek and Becker 2015.…”
Section: Introductionmentioning
confidence: 99%